An Extragastrointestinal Tumor Diagnosed as a Vaginal Mass during Pregnancy - Reo Ando; Shuichi Taniguchi; Shuji Arita; Murasaki Aman; Kousuke Marutsuka; Tomihiro Shimamoto (Case Reports in Obstetrics and Gynecology)
We report a case of an extragastrointestinal stromal tumor diagnosed as a vaginal mass during pregnancy. The mass was detected during routine examination at 24 weeks of gestation. At 26 weeks, the patient underwent transvaginal ultrasonography and magnetic resonance imaging, which revealed a blood flow-rich mass of approximately 50×30 mm in the rectovaginal septum. At 29 weeks of gestation, we resected the mass vaginally and the pathological diagnosis was a gastrointestinal stromal tumor. Chemotherapy was withheld until after full-term birth because the proliferation index of the tumor cells was low. The patient delivered a healthy infant. Imatinib was commenced at 1 month postpartum, with no recurrence or metastasis after 2.5 years. An extragastrointestinal stromal tumor as a vaginal mass in pregnancy has not been reported; however, our case suggests that the tumor should be considered a differential diagnosis of a vaginal mass in pregnancy.